Spectrophotometric Determination of Chloramphenicol in Pure and Pharmaceutical Formulations - Thangadurai, S.; Y. Anjaneyulu, Y.; Shukla, S.K. (Asian Journal of Chemistry, 2010)
A simple and sensitive spectrophotometric method has been developed for the determination of chloramphenicol (CAP) in bulk and in pharmaceutical formulations. The proposed method involves reduction of the analyte with Zn-HCI followed by diazotisation and coupling of the resulting diazonium salt with resorcinol in alkaline medium to form a coloured chromogen. The results of analysis of this method have been validated statistically and found to be precise and accurate.